Mechanisms linking prenatal environment and linear growth: the case of Ramadan during pregnancy - Pradella, Fabienne; Ewijk, Reyn van (American journal of epidemiology, 2025)
Despite established links between prenatal nutritional deprivation and impaired offspring growth, the underlying dynamics and potential moderators remain largely unexplored. This study investigates the dynamics underlying Ramadan during pregnancy and its associations with children’s linear growth, using data from the Indonesian Family Life Survey (1993-2015). We exploit Ramadan during pregnancy as a natural experiment, separating exposure from maternal background characteristics and season of birth effects. Using ordinary least squares and logistic regressions, we explore 2 key mechanisms predicted by medical theory. First, the realization of health impairments in response to prenatal shocks is influenced by postnatal circumstances. Our results reveal significant growth impairments primarily in children raised in poor sanitary conditions, which, by itself, is a risk factor for diminished linear growth. Second, we assess whether prenatal exposure to Ramadan prompts epigenetic shifts toward earlier reproductive activity, potentially at the expense of height growth. Our data show that women prenatally exposed to a Ramadan tend to have their first childbirth at a younger age, though menarche onset remains unaffected. These results suggest postnatal environments play a crucial role in mitigating sensitivity to prenatal shocks, highlighting the critical need for favorable living conditions for all children.
Online verfügbar: 04. Oktober 2024, Artikelversion: 06. Mai 2025
Gesehen am 16.10.2025